Careers in International Affairs, Ninth Edition - Laura E. Cressey, Barrett J. Helmer, and Jennifer E. Steffensen (Georgetown University Press, 2014)
This book is intended to assist those seeking a career in the international affairs community. From my position as a career and internship coordinator at Georgetown University’s Master’s of Science in Foreign Service (MSFS) program, and my coeditors’ positions as graduate students in the MSFS program, much of the content of the book is written with undergraduate and graduate students in mind. But we hope that young professionals, those seeking a career change, and those at an even earlier place in their academic pursuits will also find value in the discussion of the different sectors and organizations in which one can find challenging and enriching internationally focused positions and careers. Ironically, I used an earlier edition of this book while I was in college and was trying to figure out where to go to graduate school and how to make sense of all the government agencies involved in national security issues. Admittedly, I focused on only one section of the book—the US government and, to some extent, international organizations—given my firm desire to work for the federal government. But my career path to date, which began at the State Department working primarily on nonproliferation issues and then meandered to consulting and to Georgetown, is one that I could not have predicted while thumbing through the pages of this book. Yet I have since discovered that careers spanning the public, private, and nonprofit sectors are more frequent than not. In perusing this book I hope that you recognize that which I often try to convey to my graduate students: Opportunities in a particular field or function do not exist just in one organization, or even in one sector, but usually exist across multiple organizations and sectors. Taking my original focus of nonproliferation, for example, I could have found opportunities in the US government (e.g., in the State, Defense, Commerce, and Energy departments; the intelligence community, the Treasury Department, the Office of Management and Budget, and the US Congress); in the private sector, with any number of consulting firms and government contractors; in international organizations (in the United Nations, the International Atomic Energy Agency, and the Organization for the Prohibition of Chemical Weapons); and in numerous nonprofits, think tanks, and universities. It is extremely easy—and common, as I have repeatedly witnessed—for a person to focus his or her job search on attaining the one perfect job at one specific organization. Hopefully, what you will take away from this book is that it is advisable (and perhaps even essential) to broaden your perspective and be as inclusive as possible in your search for a career in international affairs.